Exploring Students' Experience of Using Nearpod in Grammar Lesson in Relation with Students’ Increased Engagement: A Descriptive Qualitative Approach - Atik Astrini; Agus Wijayanto; Malikatul Laila (Publikasi Indonesia, 2024)
The research aims to investigate the student’s experience of using Nearpod related to students’ increased engagement in grammar lesson at SMAN 1 in Surakarta. The significant level of engagement is the key for students to keep up with grammar lesson and then gain better comprehension of the lesson. The research uses descriptive - qualitative method. The research applies focus group discussion, in-depth interview, observation techniques and document analysis. To broaden understanding about the level of engagement, the research explores the students’ experiences in learning grammar using Nearpod. The research then analyzes the data from techniques to identify the pattern, trend, theme and meaning. The result of the research shows that the use of Nearpod in Grammar Lesson has significant impact in increasing students’ engagement. This finding implies the important of integrating subjects with digital platforms to create collaborative and interactive environment of learning